Editors' Prelude to Microbiome Research Reports. - Ventura M; van Sinderen D; Turroni F; Milani C; Munoz J; Haller D; Ross RP; Collado MC; Allen-Vercoe E; Del Rio D; Altermann E; Katayama T; et al. (OAE Publishing, 2021)
It is our sincere pleasure to introduce a new scientific journal named Microbiome Research Reports (acronym MRR), born out of an ambitious initiative from the Editorial Board of this new journal. Our motivation to initiate a new journal on microbiome research was driven by the importance and impact of the microbiome for human and planetary health, with related research interest and effort driven by the scientific community on the subject. In fact, research findings on this subject represent a Copernican Revolution influencing all research branches of the Life Sciences. For example, vast efforts are currently invested in elucidating potential links between microbiome and disease, which could lead to the discovery of microbial biomarkers for novel therapeutic and preventative strategies. We feel that it is very timely to launch a new journal focusing on Microbiome studies in humans and other animals, i.e., both wild- and domesticated- animals, being convinced that it will be a platform for the dissemination of microbiome discoveries.